The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/stem.1419
|View full text |Cite
|
Sign up to set email alerts
|

KIT Receptor Gain-of-Function in Hematopoiesis Enhances Stem Cell Self-Renewal and Promotes Progenitor Cell Expansion

Abstract: The KIT receptor tyrosine kinase has important roles in hematopoiesis. We have recently produced a mouse model for imatinib resistant gastrointestinal stromal tumor (GIST) carrying the Kit V558D and Kit T669I (human KIT T670I ) mutations found in imatinib-resistant GIST. The Kit V558D;T669I/1 mice developed microcytic erythrocytosis with an increase in erythroid progenitor numbers, a phenotype previously seen only in mouse models of polycythemia vera with alterations in Epo or Jak2. Significantly, the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The RNA-seq analysis indicated that Samd14 knockdown decreased c-Kit expression in erythroid precursor cells (R1) (~1.4 fold, q = 0.04), and c-Kit promotes HSPC self-renewal (Deshpande et al, 2013). Transferrin receptor ( Tfrc ), Cd47 , Epo receptor ( Epor ) and Flt3 were unchanged (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA-seq analysis indicated that Samd14 knockdown decreased c-Kit expression in erythroid precursor cells (R1) (~1.4 fold, q = 0.04), and c-Kit promotes HSPC self-renewal (Deshpande et al, 2013). Transferrin receptor ( Tfrc ), Cd47 , Epo receptor ( Epor ) and Flt3 were unchanged (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…AKT activation can mediate c-Kit signaling (Blume-Jensen et al, 1998; Ma et al, 2012b) and SCF/c-Kit signaling stimulates HSPC self-renewal (Deshpande et al, 2013). GATA-1 repression and GATA-2 activation of Kit correlates with occupancy of an intron 1 and an upstream cis -element, respectively (Jing et al, 2008; Munugalavadla et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly however dasatinib did not affect the numbers of hematopoietic stem cells (HSC) or progenitors. This was unexpected given dasatinib's ability to inhibit c-Kit, and the in vivo requirement of these cells for c-Kit signaling [14][15][16]. We did however find that serum from dasatinib-dosed mice showed higher levels of stem cell factor (SCF), i.e.…”
Section: Introductionmentioning
confidence: 83%
“…In addition, we found that the number of white blood cells (WBCs) and lymphocytes (LYMs) was over twofold higher in KIT Dup/+ mice than that in WT mice ( Supplementary Table S3 and Figure S4). A previous study found that a gain-of-function KIT mutation promoted myeloid progenitor expansion, and lead to an increased number of WBCs (Deshpande et al, 2013). Therefore, unlike the situation in skin tissue, the KIT CDS duplication may have a stronger effect on PI3K and MAPK signaling in the hematological system, thus leading to an increase in the number of WBCs.…”
Section: The Kit Splice Mutation Impairs the Kinase Activity Of The Kmentioning
confidence: 96%